2016
DOI: 10.3102/0034654316653478
|View full text |Cite
|
Sign up to set email alerts
|

The Theoretical and Empirical Basis of Teacher Leadership

Abstract: In the current review, we examined teacher leadership research completed since York-Barr and Duke published the seminal review on teacher leadership in 2004. The review was undertaken to examine how teacher leadership is defined, how teacher leaders are prepared, their impact, and those factors that facilitate or inhibit teacher leaders' work. Beyond this, the review considered theories informing teacher leadership, teacher leadership within disciplinary contexts, and the roles of teacher leaders in social jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
570
2
33

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 544 publications
(624 citation statements)
references
References 57 publications
(154 reference statements)
19
570
2
33
Order By: Relevance
“…When the findings are considered as a whole, the level of performing teacher leadership behaviors being over the moderate level can be evaluated as a positive aspect. This is because positive changes are observed in school development (Poekart, 2012;York-Barr & Duke, 2004;Wenner & Campbell, 2016) and teacher effectiveness (Harris & Muijs, 2005) depending on teacher leadership. On the other hand, teacher leadership behaviors being perceived over a certain level can be related to various organizational and personal variables.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
See 4 more Smart Citations
“…When the findings are considered as a whole, the level of performing teacher leadership behaviors being over the moderate level can be evaluated as a positive aspect. This is because positive changes are observed in school development (Poekart, 2012;York-Barr & Duke, 2004;Wenner & Campbell, 2016) and teacher effectiveness (Harris & Muijs, 2005) depending on teacher leadership. On the other hand, teacher leadership behaviors being perceived over a certain level can be related to various organizational and personal variables.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…In a seminal work that analyzed 140 studies on teacher leadership, York-Barr and Duke (2004) categorized the duties of leading teachers as ensuring coordination between school and administration, assisting in the professional development of colleagues, participating in the process of school development, ensuring the participation of parents and the environment, contributing to the teaching profession, and providing preservice teacher training. In another study, Wenner and Campbell (2016) analyzed 54 studies and revealed that teachers who assume leadership roles make other teachers feel supported, encourage professional development and growth, and make significant contributions to the changes that take place in schools.…”
Section: What Is Teacher Leadership?mentioning
confidence: 99%
See 3 more Smart Citations